PENGARUH WAKTU APLIKASI DAN KONSENTRASI GIBERELIN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN GANDUM (Triticum aestivum L.) PADA DATARAN MEDIUM - Yusanti F; Wicaksono F Y; N Tati (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2017)
Giberelin can reduce the effects of heat stress on wheat crops grown medium height. This experiment was aimed the concentration of gibberellin and the effective application time of gibberellin to give the best response of yield components in wheat. The experiment conducted from 2 November 2016 until 2 February 2017 at Ciparanje experiment field, Faculty of Agriculture, University of Padjadajaran, with an altitude of 795 metres above sea level. The experimental design used a Randomized Completely Block Design with factorial pattern which consisted of two factors and two replication. First factor was consentration gibberellin consisted of three levels : 250 ppm, 350 ppm and 450 ppm. Second factor was time application that consisted of 10, 25, 40, 55 and 70 Days After Planting. The results of this research showed that there were interaction effect on number of grains per panicle and weight 100 grain. Concentration of gibberellin hormone 350 ppm affected the number of filled grain per panicle in 25 Days After Planting. Furthermore, the weight of 100 grains showed the highest yield at concentration 450 ppm gibberellin hormone with a level of application time 10 Days After Planting.Keywords : Wheat, Gibberellin, Time application